Heparan sulfate proteoglycans are ligands for receptor protein tyrosine phosphatase sigma. - Aricescu, A; McKinnell, I; Halfter, W; Stoker, A (2002)
RPTPsigma is a cell adhesion molecule-like receptor protein tyrosine phosphatase involved in nervous system development. Its avian orthologue, known as cPTPsigma or CRYPalpha, promotes intraretinal axon growth and controls the morphology of growth cones. The molecular mechanisms underlying the functions of cPTPsigma are still to be determined, since neither its physiological ligand(s) nor its substrates have been described. Nevertheless, a major class of ligand(s) is present in the retinal basal lamina and glial endfeet, the potent native growth substrate for retinal axons. We demonstrate here that cPTPsigma is a heparin-binding protein and that its basal lamina ligands include the heparan sulfate proteoglycans (HSPGs) agrin and collagen XVIII. These molecules interact with high affinity with cPTPsigma in vitro, and this binding is totally dependent upon their heparan sulfate chains. Using molecular modelling and site-directed mutagenesis, a binding site for heparin and heparan sulfate was identified in the first immunoglobulin-like domain of cPTPsigma. HSPGs are therefore a novel class of heterotypic ligand for cPTPsigma, suggesting that cPTPsigma signaling in axons and growth cones is directly responsive to matrix-associated cues.